Bernstein-type inequalities for splines defined on the real axis - Babenko, V. F.; Zontov, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We obtain the exact inequalities of the Bernstein type for splines s S_m, h L_2 (R) as well as the exact inequalities that, for splines s S_m, h, h > 0, estimate L_p-norms of the Fourier transforms of their k-th derivative by L_p-norms of the Fourier transforms of splines themselves.